2014
DOI: 10.1080/02786826.2014.957755
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Granular Ceramic Filter and Prediction of Its Collection Efficiency

Abstract: The silicon carbide (SiC) ceramic filter is the most favorable component to remove particulate matter from hot flue gas due to its high filtration efficiency and high thermal durability. The effect of SiC powder size on the physical properties and filtration performance to prepare high-performance granular ceramic filter media was investigated in this study. Disk-type filter media were prepared by mixing ceramic components followed by physical compression and sintering. The porosity and average pore diameter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…The mechanical strength was measured using a universal testing machine (UTM) (KDMT-156, Kyung Do Precision). A special jig was also used to hold a thin ceramic filter based on our previous study [3]. The crystallinities and phase transitions of the ceramic filters were examined by X-ray diffraction (XRD) (X'Pert Pro MPD diffractometer, PANalytical CO.) using Cu-Kα radiation.…”
Section: Characterization Of Ceramic Filtersmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanical strength was measured using a universal testing machine (UTM) (KDMT-156, Kyung Do Precision). A special jig was also used to hold a thin ceramic filter based on our previous study [3]. The crystallinities and phase transitions of the ceramic filters were examined by X-ray diffraction (XRD) (X'Pert Pro MPD diffractometer, PANalytical CO.) using Cu-Kα radiation.…”
Section: Characterization Of Ceramic Filtersmentioning
confidence: 99%
“…Ceramic filters can be applied to remove particulate matters in hot flue gas from coal-fired power plants, especially pressurized fluidized bed combustion (PFBC) systems and integrated gasification combined-cycle (IGCC) systems [1][2][3]. Moreover, efficient hot gas filtration becomes more important to protect downstream equipment for effective energy recovery and gas separation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that filtration efficiency was increased with the degree of sphericity. Choi et al (2014) investigated the influence of the granular size and its distribution on filtration efficiency and pressure drop. However, their approaches could not focus on the relationship between heterogeneity and filtration efficiency.…”
Section: Introductionmentioning
confidence: 99%